Exploring Ecotourism Concept In Social Media For Students At Smk Swasta Kristen Tomosa 2 - Telaumbanua, Yarlin Nurlina; Hulu, Juni Hati Kristiani; Zebua, Fetry Shelvian (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to explore the strategy of implementing social media in introducing the concept of ecotourism to students of SMK Swasta Kristen Tomosa 2. This research is descriptive with a qualitative approach, with the research location at SMKSwasta Kristen Tomosa 2. The research used an online questionnaire with Google Form. The results showed that social media proved to be an effective tool to reach students and convey information about ecotourism. Facebook is the social media platform that they often use. Social media can raise awareness about the importance of environmental conservation and encourage student participation in ecotourism activities. This study provides several suggestions to improve the effectiveness of using social media in ecotourism education. These suggestions include utilizing social media platforms that are popular among students, developing interesting and informative content, using relevant hashtags to expand reach, and monitoring and evaluating the effectiveness of social media. Thus, it is hoped that students can gain a better understanding of the concept of ecotourism and actively participate in environmental conservation efforts.